THE ECONOMY OF IMPRESSIONS AS A DRIVER OF TOURISM DEVELOPMENT IN THE CONTEXT OF GLOBAL CHALLENGES - Rogach, Olga; Frolova, Elena; Shcherbachenko, Petr; Danilova, Veronika; Duborkina, Irina (Revista Inclusiones, 2020)
The complex epidemiological situation in the world has caused a crisis in the tourism industry. Falling incomes, a high degree of uncertainty in the labor market, and the general depressed state of the economy will undoubtedly change the face of modern tourism. The authors aim to determine the sources of tourist demand in the context of global challenges; taking into account the provisions of the economy of impressions to identify the key drivers of the development of the tourist market. The Internet survey of citizens living on the territory of Moscow (N=219) was used as the leading research method. The obtained materials were supplemented with the results of a focus group study. The main predictor of tourist choice is the assessment of the visual attractiveness of the tour, its exclusivity, the ability to visualize and replicate your own travel experience. The commercialization of the process of impression consumption involves the exploitation of hedonistic needs, the value of aesthetic satisfaction, and the development of interactive and communicative practices aimed at creating positive emotions for tourists.